Psychological Distress and Homesickness Among Sudanese Migrants in the United Arab Emirates - Hamid, Abdalla A. R. M. (Frontiers in Psychology, 2022)
Migration is a global phenomenon growing in scope, and it can be associated with negative emotions such as a sense of impending loss, fear of the unknown, and anxiety about those left at home. The objective of this exploratory study was to examine psychological distress and homesickness among Sudanese migrants in the United Arab Emirates (UAE). Participants were 1444 Sudanese migrants (mean age = 40.20; SD = 10.98). The Second Version of the Dundee Relocation Inventory was used to assess homesickness, and the 28-item General Health Questionnaire was used to measure psychological distress, depressive and anxiety symptoms, somatic symptoms, and social dysfunction. The results showed that older age and longer duration of residence in the UAE were associated with lower levels of homesickness, psychological distress, and depressive and anxiety symptoms. Further, homesickness was associated with higher psychological distress, somatic symptoms, and depressive and anxiety symptoms. Women and unemployed migrants had higher psychological distress, somatic symptoms, and depressive and anxiety symptoms compared with men and those employed, respectively. Being unmarried was associated with higher levels of depressive symptoms and homesickness, while those married or divorced/widowed showed lower levels of depressive symptoms and homesickness. It was concluded that there is a need to tackle unemployment among migrants in the UAE and address family reunion issues.